Management of HR benefits in the public service: the case of the Department of Cooperative Governance, Human Settlements and Traditional Affairs in the Limpopo Province - Sepuru, Pharudi Paulinah (My University, 2013)
The aim of this study was to examine the implementation of HR Benefits in the public sector through grey and secondary literature, semi-structured questionnaires and interviews. These methods yielded the same results in the majority of cases and corroborated much that was raised in the literature review. However, there were instances where they negated each other and some of the views of certain commentators. This is where the hands-on experience of the author became invaluable to clarify these contradictions. Amongst other key findings of the study were that employee benefits were and are still wrongly managed; the subjective assessment of employee performance for performance bonus and the scaling down of the percentages scored by employees to accommodate the wage bill had the effect of dampening employee morale. It is hoped that various government departments will draw valuable lessons from this case study and adopt good practice to perfect the management of employee benefits.
Thesis (MPA.) -- University of Limpopo, 2013
Keywords: Absenteeism; Health Risk Manager; Housing allowance; HR Benefits; Incapacity leave; Leave; Medical aid; Perception; Performance bonus; Pensions; Personnel departments -- Employees; Performance -- Evaluation; Performance -- Management